Hubungan antara self-esteem dengan perhubungan perkahwinan - Bong, Set Foon (Universiti Malaysia Sarawak, UNIMAS, 2007)
The purpose of this research is to study the relation between self-esteem and marital relationship among nurses in the General Hospital Kuching, Sarawak. This study finds out the relation between self- esteem with communication, role achievement and task achievement and also relation between self-esteem with selected demographic factors such as gender and marital duration. This study included 82 nurses. A descriptive statistic method was used to get the frequency and percentage for the demographic factors while the t-test, ANOVA and Spearman correlation was used to test the hypothesis of this research. The result of the correlation analysis showed that there are no significant relation between self-esteem and marriage. Only selected demographic factors that are gender an d marital duration showed a significant relation with self- esteem. The researcher recommended some suggestion to General Hospital Kuching, Sarawak, counseling professionals and future.